Evaluasi Atas Implementasi Aplikasi Sistem Aplikasi Instansi Berbasis Akrual (SAIBA) Pada Satuan Kerja Lingkup Pembayaran KPPN Samarinda - Rina Masithoh Haryadi, Ridaan Shari Titin Ruliana 2 (EKONOMIA, 2021)
This research was conducted to determine whether system quality, information quality, and service quality affect user satisfaction of the Accrual-Based Agency Accounting System application in work units in the KPPN payment area of Samarinda City partially and simultaneously.The analytical tools used in this research are validity test, reliability test, classic assumption test which consists of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, multiple linear regression analysis, F statistical test, and t statistical test.The results of the analysis that have been carried out show that the System Quality (X1) and Information Quality (X2) variables have a positive and significant effect on User Satisfaction (Y), while the Service Quality variable (X3) has a positive and insignificant effect on User Satisfaction (Y).The better quality of the SAIBA information system which is represented by ease of use, reliability, fast access, flexibility, and a high level of security, the more user satisfaction with the application will be. The better the quality of information produced in the form of information that is accurate, reliable, relevant, easy to understand, and timely, the higher the level of satisfaction of application users, because the SAIBA application is made to produce financial reports as a form of accountability for the budget that has been used by each. each agency. Service quality is not a variable that significantly affects the level of user satisfaction, but there is a positive influence between service quality and user satisfaction which indicates that the better the quality of service provided by KPPN officers in informing the implementation of the SAIBA application provided, it will increase user satisfaction. User perceptions in measuring the satisfaction level of using the SAIBA application are not on how KPPN officers provide information about application implementation, but rather on the quality of the application itself and how the quality of information generated by the application.